FRI0336 Belief about medicine questionnaire predicts therapeutic adhesion to hydroxychloroquine during systemic lupus erythematosus. (12th June 2018) - Rozban, Y.; Devilliers, H.; Hié, M.; Micheline, P.; Mathian, A.; Cohen-Aubart, F.; Julien, H.; Zahr, N.; Amoura, Z.
Abstract : Background: Therapeutic adherence is a key element of chronic disease management and one of the most difficult to assess. The Belief about Medicines Questionnaire (BMQ) evaluates patients' own beliefs related to medication. It is available in two sections: the BMQ-General and the BMQ-Specific. The BMQ-specific focuses on the representations of medication prescribed for personal use. It was set up as a screening test for poor therapeutic adherence during certain chronic diseases. Early detection of lupus patients at risk of poor therapeutic adherence could lead to preventive actions. Objectives: To assess the BMQ-Specific as a predictive test of adherence to hydroxychloroquine in SLE. Methods: Case-control, retrospective and monocentric study. Cases were enrolled according to the following criteria: systemic lupus erythematosus (SLE) according to the ACR classification criteria and HCQ dosage <100 ng/ml after a minimum of 2 months of treatment. The matched control was a lupus patient, enlisted within the centre the same week, with a HCQ dosage ≥800 ng/ml. Each patient answered the BMQ-Specific through a telephone interview. The BMQ-Specific comprises two 5-item factors assessing beliefs about the necessity of prescribed medication ( Specific-Necessity ) and concerns about the danger of dependence and long-term toxicity of medication ( Specific-Concerns ). Responses to each statement were scored on a five-point Likert scale (1=strongly disagree and 5=strongly agree). Scores obtained for the individual items within both scales were summed to give total scores for the Specific-Necessity and Concerns scales range from 5 to 25. A Necessity–Concerns (N-C) differential was calculated (range from −20 to +20). It expresses the cost–benefit perceived by the patient for taking the medication. Case and control characteristics were compared using usual tests. Diagnosis performance of each BMQ score and necessity-concern differential were studied by the mean of ROC curves. Results: The BMQ-Specific questionnaire was submitted to 118 patients: 59 cases and 59 matched controls. The concern score was significantly higher in cases (mean 16.8 vs. 12.7, p<0.0001). The necessity score was significantly higher in control (mean 18.4 vs 15, respectively, p<0.0004). ROC curves show a better area under the curve (AUC) with the N-C differential compared to the AUC of separate scores (respectively 0, 8 vs 0, 7). The sensitivity and specificity are optimal for a N-C differential of 3. Conclusions: During SLE, nonadherent patients are primarily concerned about the risks inherent to treatment, rather than its effectiveness. To date, we are the only study to show that specific BMQ is an efficient tool for detecting patients at risk of poor therapeutic adherence to HCQ during SLE. The necessity-concerns differential score must be preferred to the scores taken separately. Thus, targeted educational actions can be provided as soon as the patients are taken in charge, in order to improve their adherence to treatment. Disclosure of Interest: None declared